MBRS-42. GMYC: A NOVEL INDUCIBLE TRANSGENIC MODEL OF GROUP 3 MEDULLOBLASTOMA. Issue 2 (22nd June 2018) - Weishaupt, Holger; Mainwaring, Oliver; Hutter, Sonja; Kalushkova, Antonia; Jernberg-Wiklund, Helena; Rosén, Gabriela; Swartling, Fredrik J
Abstract: Group 3 medulloblastoma (MB) carry the worst prognosis of all MB. The transcription factors MYC and MYCN have been suggested as drivers for a subset of these tumors, with MYC amplifications (17-20%) representing the most common genetic alteration in Group 3 tumors, while MYCN amplifications (4-6%) are less frequent. In order to study MYC / MYCN -driven Group 3 MB and improve current treatment options for these patients, it is of crucial importance to decipher differential features of MYCN - and MYC -driven tumors and to establish accurate animal models for both groups of patients. Driving MYC from the hindbrain-specific Glutamate transporter 1 ( Glt1 ) promoter using a Tet-OFF system we have established a novel murine model of spontaneous MYC -driven MB (GMYC), which accurately recapitulates aggressive Group 3 MB. GMYC tumours develop with 70% penetrance and tumor-prone GMYC mice can be cured by MYC -depletion through dox treatment. Comparison of transcriptional profiles between GMYC and our MYCN -driven GTML tumors revealed that both models accurately represent Group 3 MB, while showing differential expression of key features of MYC - or MYCN -driven tumours. CDKN2A was identified as one of the top upregulated genes in our GTML model as compared to our GMYC model. CDKN2A encodes the tumor suppressors p16INK4A and p14ARF, which act as key regulators of cell cycle progression and activation/stabilization of p53. Similar enhancement of this gene was observed in MYCN -amplified as compared to MYC -amplified Group 3/4 patients. Ongoing analyses will explore the effects on tumour formation/progression following partial or complete knockout of CDKN2A in both mouse models.